Thermal and morphological properties of thermotropic liquid‐crystalline copolyesters containing poly(ethylene terephthalate), 4‐hydroxyphenylacetic acid and main‐chain rigid aromatic units - Babacan, Volkan; Aksoy, Serpil; Yerlikaya, Zekeriya; Altınok, Haydar (Wiley, 2010)
AbstractThermotropic liquid‐crystalline polymers (TLCPs) have aroused considerable interest due to their attractive properties as high‐performance materials. Significant research attention has been devoted to investigating the relationship among monomer structures, syntheses and end‐use properties of TLCPs. The study reported here concerns the preparation, characterization and melt spinning of novel copolyesters containing two different flexible units together with two different aromatic units in the polymer chains. A range of copolyesters based on p‐hydroxybenzoic acid (p‐HBA), m‐hydroxybenzoic acid, p‐hydroxyphenylacetic acid and poly(ethylene terephthalate) were synthesized. The liquid crystallinity, thermal properties and degrees of crystallinity of these copolyesters were investigated using hot‐stage polarized light microscopy, differential scanning calorimetry, thermogravimetry and wide‐angle X‐ray diffraction. Copolyester fibres were characterized using scanning electron microscopy. The copolyesters were melt‐processable, thermally stable and could be processed above their melting temperatures without degradation. The degree of crystal structure was found to depend upon the content of p‐HBA. The fibres prepared showed that polymer chains had a well‐developed fibrillar structure. Novel TLCPs containing flexible units in the main chain were synthesized and characterized. Copolyesters containing p‐HBA units ranging from 55 to 70 mol% exhibited phase‐separated liquid‐crystalline morphology, appropriate melting temperatures and high thermal stability for melt processing. Copyright © 2010 Society of Chemical Industry
Keywords: degree of crystallinity; PET; fibre; thermal properties; liquid-crystalline polymers